Update on the management of patients with intermediate and poor-risk testicular germ cell tumors and new biological insights. (2019) - Mérida-García, Antonio; Díaz-Serrano, Asunción; Bernard, Brandon; del Mar Galera, María; de Velasco, Guillermo; Sepúlveda, Juan Manuel; Fernández, Lourdes; Medina, Javier; Castellano, Daniel
Highlights: BEP remains the first-line standard treatment in patients with germ cell tumors. TIP or HDCT can provide favorable benefits in poor-risk GCT compared to BEP. An adaptive treatment may be proposed according to the decrease in serum biomarkers. Patients will receive personalized treatment based on molecular biology.